2009
DOI: 10.1002/gcc.20669
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A, NF2, and JUN are dysregulated among other genes by miRNAs in malignant mesothelioma—A miRNA microarray analysis

Abstract: Malignant mesothelioma (MM) is an aggressive cancer arising from mesothelial cells, mainly due to former asbestos exposure. Little is known about the microRNA (miRNA) expression of MM. miRNAs are small noncoding RNAs, which play an essential role in the regulation of gene expression. This study was carried out to analyze the miRNA expression profile of 17 MM samples using miRNA microarray. The analysis distinguished the overall miRNA expression profiles of tumor tissue and normal mesothelium. Differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
185
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(198 citation statements)
references
References 43 publications
9
185
1
3
Order By: Relevance
“…The reduced miR-615-3p expression was then validated in the present study using 40 matched pairs of NSCLC and normal lung tissues, and the findings were consistent with the results reported in a previous study investigating malignant mesothelioma, which identified that miR-615-3p was downregulated in NSCLC tissues (14). Another study reported that miR-615-3p was upregulated and significantly associated with overall survival time in mantle-cell lymphoma (15).…”
Section: Discussionsupporting
confidence: 90%
“…The reduced miR-615-3p expression was then validated in the present study using 40 matched pairs of NSCLC and normal lung tissues, and the findings were consistent with the results reported in a previous study investigating malignant mesothelioma, which identified that miR-615-3p was downregulated in NSCLC tissues (14). Another study reported that miR-615-3p was upregulated and significantly associated with overall survival time in mantle-cell lymphoma (15).…”
Section: Discussionsupporting
confidence: 90%
“…Human miR-483 is a microRNA located within intron 2 of the IGF2 locus. It has been found that mature miR-483-3p is overexpressed in malignant mesothelioma and Wilms' tumors [34,35]. In addition, the expression level of miR-483-3p is high or extremely high in many common adult human cancers, comprising 30% of cases of colon, breast and liver cancers [35].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the mature miRNA processed from the 3 0 arm of the stemloop miR-885 (miR-885-3p) has been previously reported in malignant mesothelioma tissues. 34 The relative underexpression of miR-885-5p in von Hippel-Lindau disease-related pheochromocytomas may be linked to the frequent loss of chromosome 3p25.3. Loss of 3p or that of whole chromosome 3 could be detected in 94% of von Hippel-Lindau disease pheochromocytomas.…”
Section: Discussionmentioning
confidence: 99%